Efficacy of Garcinia mangostana Linn. and Achyranthes aspera Linn. Combined Extracts in the Prevention of Endometritis in Cattle - So-In, C.; Khankhum, S.; Khaowong, I.; Pangchai, T.; Sunthamala, N. (Faculty of Animal Science, IPB University, 2024)
Endometritis is an important factor in cattle fertility. Pathogenicity and the development of numerous reproductive diseases are directly related to bacterial imbalance in the genital tract. A commercial antibiotic can be relatively costly and can disrupt the animal’s usual gut microflora; instead of plant medicals. The aim of this study was to develop an effective artificial insemination (AI) gel from traditional Thai herbs that exhibit bacterial inhibition. Twenty-four female Thai native cattle were divided into two groups: endometritis and healthy. Uterine swabs were isolated, identified, and tested for bacterial biofilm formation in vitro. Brucella ovis, Campylobacter fetus, Helicobacter trogontum, and Arcobacter cryaerophilus were found in female genitalia with endometritis based on weak biofilm information. Garcinia mangostana Linn. and Achyranthes aspera Linn. extracts were tested for antibacterial activity using agar dilution assay. A 10 µg/mL concentration of both extracts in combination was effective against the mixed bacterial isolation. The specific AI gel with those extracts was then developed (so-called GA-Gel) in vivo. The combined extracts inhibited the endometritis bacteria that expressed antimicrobial activity in vivo. Their hematological profiles indicated that the total white blood cells, neutrophils, and lymphocytes counts decreased (p≤0.05). Compared to healthy cattle, the treated cattle had no significant difference in the levels of aminotransferase (ALT), aspartate aminotransferase (AST), blood urea nitrogen (BUN), and creatinine. Both in vivo and in vitro indicated that the GA-Gel was effective for the prevention of an increase of bacteria and can be potentially developed to be an efficient AI gel.